An Incremental Retrieval Mechanism for Case-Based Electronic Fault Diagnosis - Cunningham, Padraig; Smyth, Barry; Bonzano, Andrea (Trinity College Dublin, Department of Computer Science, 1998)
One problem with using CBR for diagnosis is that a full case description may not be available at the beginning of the diagnosis. The standard CBR methodology requires a detailed case description in order to perform case retrieval and this is often not practical in diagnosis. We describe two fault diagnosis tasks where many features may make up a case description but only a few features are required in an individual diagnosis. We evaluate an incremental CBR mechanism that can initiate case retrieval with a skeletal case description and will elicit extra discriminating information during the diagnostic process.
To Appear in Journal of Knowledge Based Systems
Keywords: Case-based reasoning; case retrieval; electronic fault diagnosis